Factors Influencing Choice of Traditional Bone Fracture Treatment Choice of Patients in East Deli Tua - Silalahi, Rini; Ansela, Rasninta Devi (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2026)
Introduction: Traditional medicine is still widely practiced by the community despite the increasing development of modern health services. This study aims to analyze the factors influencing the choice of traditional bone fracture treatment in fracture patients in East Deli Tua in 2025. Methods: The study design used a cross-sectional method. The study sample consisted of 55 respondents selected using a purposive sampling technique. The instrument used was a Likert scale questionnaire that measured knowledge, socio-cultural factors, family support, ecnomic, and psychological factors. Results: The results showed that the majority of respondents had a low level of knowledge (41.8%), weak socio-cultural influence (45.5%), sufficient family support (34.5%), and sufficient economic conditions (41.8%). Bivariate analysis showed that all independent variables had a significant relationship with the choice of traditional medicine (p-value <0.05). The most dominant factors influencing patient decisions were family support and economic considerations. Conclusion: The conclusion of this study is that the choice of traditional medicine in fracture patients is influenced by a combination of internal and external factors, especially knowledge, culture, family support, economic, and psychological conditions of the patient. The findings of this study have important implications for nursing practice, particularly in improving patient-centered fracture care, health education, and culturally sensitive interventions for individuals with fractures.